Calculation of loads during operation of tower cranes - Gorbatyuk, Ievgenii; Hokh, Vladyslav (КНУБА, 2024)
In order to simplify calculations of structures under dynamic loads in operation, a diagram is given according to which the rest of all elements of the mechanism are brought to its first element (engine). This allows you to greatly simplify the equation for solving and determine the values of the elasticity or stiffness factors of the elements.
Keywords: crane; mechanism; indicator; element; load; moment; 621.873.7